2018
DOI: 10.14800/mr.1518
|View full text |Cite
|
Sign up to set email alerts
|

Platelet rich plasma in osteoarthritis: More than a growth factor therapy

Abstract: Osteoarthritis (OA) is the most commonly encountered degenerative joint disorder in clinical medicine and the pain and stiffness caused by osteoarthritis represents a leading cause of physical disability in individuals of retirement age. Treatment options for OA patients are limited and largely targeted to pain management. Such is the mechanism behind the most commonly prescribed OA therapies including acetaminophen, NSAIDs, opioids, and steroids. However, these palliative pain management tools do not address … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…22 It has grown ever since and been applied to the fields of orthopaedics, dermatology, plastic surgery, odontology and even veterinary medicine. 23 This biological product derived from autologous blood centrifugation contains a mixture of a variety of cells with a primary focus on concentrated platelets above baseline 24,25 and is obtained via the use of commercial kits or in house techniques, resulting in different PRP products and, therefore, different terminologies. 23 The platelets present in PRP contain granules with a broad range of active biomolecules which, upon activation, release these biomolecules, therefore stimulating the natural healing cascade.…”
Section: Biological Perspective Of Osteoarthritismentioning
confidence: 99%
“…22 It has grown ever since and been applied to the fields of orthopaedics, dermatology, plastic surgery, odontology and even veterinary medicine. 23 This biological product derived from autologous blood centrifugation contains a mixture of a variety of cells with a primary focus on concentrated platelets above baseline 24,25 and is obtained via the use of commercial kits or in house techniques, resulting in different PRP products and, therefore, different terminologies. 23 The platelets present in PRP contain granules with a broad range of active biomolecules which, upon activation, release these biomolecules, therefore stimulating the natural healing cascade.…”
Section: Biological Perspective Of Osteoarthritismentioning
confidence: 99%
“…PRP is defined as an autologous preparation obtained from the centrifuged peripheral blood of patients with a concentration that is 2-5 times greater than the basal concentration [38][39][40][41]. This orthobiologic product can be processed manually or with the assistance of commercial kits; however, since there are many different protocols in the literature there is a lack of consensus regarding an idealistic preparation of PRP.…”
Section: Prpmentioning
confidence: 99%
“…The benefits associated with PRP therapy, for example, were long believed to be only a result of the relative abundance of growth factors and their individual biological roles (Table 2). However, further research showed that PRP also promoted important secondary effects, including inflammatory modulation [38,[57][58][59][60], anticatabolic activity [61], normalization of integral autophagy [62,63], cytokine regulation [64][65][66], and pro-anabolic stimuli [67][68][69]. More importantly, it is also directly involved in fibrinolytic reactions, which are a key step in the resolution of tissue injury [70].…”
Section: Prpmentioning
confidence: 99%